Upaya Meningkatkan Kreativitas Anak Usia 5-6 Tahun Melalui Media Loose Parts di TK Lely Medan Jl. Tuamang GG. Mesjid, Siderojo Hilir, Kec. Medan Tembung, Kota Medan - Wiwik Indah Handayani; Nurmawati; Inom Nasution (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research aims to find out: (1) Loose Parts media can increase creativity at Lely Medan Kindergarten, (2) Implementation used to increase creativity in early childhood by using Loose Parts media at Lely Medan Kindergarten, (3) Intelligence of children aged 5- 6 years can be increased through the Loose Parts game at Kindergarten Lely Medan for the 2023-2024 school year. The research technique used was PTK (classroom action research). The subjects in this study were 10 children aged 5-6 years. Lely Kindergarten Medan Jl. Tuamang GG. Mosque, Siderojo Hilir consisting of 5 boys and 5 girls. The target for success in this research is if the percentage calculation shows that 80% of children experience an increase in children's creativity through Loose Parts media. The results of the research show that children's creativity increases after takingaction through Loose Parts media. When pre-action observations were carried out, the percentage of creativity was 28.92%, then it increased in cycle I by 46.42% and in cycle II it also increased by 81.78%. The steps taken to increase children's creativity are: opening activities, core activities and closing activities. Providing active direction is carried out during core activities and rewards are given during closing activities.